Exploring women's exposure to marketing of commercial formula products: a qualitative marketing study from two sites in South Africa. Issue 1 (31st December 2022) - Pereira-Kotze, Catherine; Horwood, Christiane; Haskins, Lyn; Kingston, Gillian; Luthuli, Silondile; Doherty, Tanya
ABSTRACT: Background: Regulating the marketing of commercial formula products is a long-term commitment required to protect breastfeeding. Marketing strategies of formula manufacturers, retailers and distributors evolve at a rapid rate. Objective: The aim of this research was to describe exposure of pregnant women and mothers of young children in South Africa to marketing of commercial formula products, compared to international recommendations and national legislation. Methods: Using mobile phone marketing diaries twenty participants in Cape Town and Johannesburg documented the formula marketing they were exposed to for one week. Ten mothers were interviewed to explore their perceptions towards marketing exposure in more depth. Results: Women reported limited infant formula advertising, but an abundance of strategies used to market growing-up formula and powdered drinks for children over 36 months. Strategies included product packaging, in-store displays, online distribution channels and educational material about product ranges. Online strategies were reported, namely social media marketing (sponsored adverts and support groups), websites and mobile phone applications providing infant and young child feeding information and price discounts, print and TV advertisements, and competitions. Products for children over 36 months are cross-promoted with products prohibited to be advertised by national legislation. Conclusions: South African women are being exposed to covert marketing of infant, follow-up, and growing-up formula. Explicit marketing of products for children over 36 months of age allows formula companies to provide messages about branding and use of commercial formula products to mothers. National legislation should be updated and effectively implemented to address changing marketing strategies.